2017
DOI: 10.1097/jnr.0000000000000168
|View full text |Cite
|
Sign up to set email alerts
|

A Prenatal Coparenting Intervention With Unmarried Father–Mother Dyads: Fidelity of Intervention Delivery by Male–Female Community Mentor Teams

Abstract: Background: Most prenatal preventive interventions for unmarried mothers do not integrate fathers or help the parents plan for the development of a functional coparenting alliance after the baby’s arrival. Furthermore, properly trained professionals have only rarely examined the fidelity of these interventions. Purpose: This report examines whether experienced community interventionists (home visitors, health educators, fatherhood service personnel) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…As was the FIOC program itself, the manual was vetted for content by Black lay and pastoral counselors, seasoned activists, community organizers, and community leaders, all residents of a southern U.S. city where the program was delivered, in collaboration with the second and fifth authors of this report. Adherence to the program manual has been formally investigated in prior research and has been shown to be uniformly strong for both male and female users (see Salman-Engin et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…As was the FIOC program itself, the manual was vetted for content by Black lay and pastoral counselors, seasoned activists, community organizers, and community leaders, all residents of a southern U.S. city where the program was delivered, in collaboration with the second and fifth authors of this report. Adherence to the program manual has been formally investigated in prior research and has been shown to be uniformly strong for both male and female users (see Salman-Engin et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…48 In the majority of the studies, researchers implemented programs in hospital settings, with outcomes based on parents' selfreports. Some researchers delivered the intervention at the group level, 35 -40, 48, 55 couple level, 43,49,52 or individual level. 10,42,45,46 Studies also differed in whether researchers used a manualized curriculum, who delivered the sessions (eg, nurse versus social worker), when the sessions were delivered (eg, before birth versus after birth), and mode of intervention delivery (eg, in-person versus mobile application) (for details see Table 2).…”
Section: Figurementioning
confidence: 99%
“…Researchers for 4 quantitative (2 RCTs and 2 quasi-experimental) and 1 qualitative studies examined fathers' mental health outcomes. 38,47,49,53 The results of a low RoB quasi-experimental study of a general education program 38 revealed significant increases in fathers' social support seeking related to pregnancy-related stressors measured during the third trimester. It was reported in a qualitative study of a relationship program intervention that occurred during pregnancy 51 that fathers felt improved emotion regulation and greater relaxation, peace, and enjoyment after the intervention.…”
Section: Father's Mental Healthmentioning
confidence: 99%
“…A systematic review conducted by Lee et al (2018) found 19 interventions for fathers-delivered in the United States-during the perinatal period that had been tested using experimental or quasiexperimental designs. These interventions focused on general childbirth education and infant care, co-parenting skills, or case management with only four examining mental health outcomes (Diemer, 1997;Feinberg and Kan, 2008;Field et al, 2008;Salman-Engin et al, 2017). Of the four interventions that assessed paternal mental health, improvements in mental health were found only by Field et al (2008) who generated reductions in paternal depressive symptoms via an intervention that taught fathers how to provide massages for their partner aimed at reducing pain and improving dyadic relationship quality.…”
Section: Introductionmentioning
confidence: 99%